Workshop Pembuatan Video Pembelajaran Kreatif Bagi Guru Matematika SMP Se-Kota Mataram - Syahrul Azmi; Ketut Sarjana; Junaidi Junaidi; Ratna Yulis Tyaningsih; Wahidaturrahmi Wahidaturrahmi (Rengganis Jurnal Pengabdian Masyarakat, 2021)
This community service activity aims to improve teachers’ abilities to create video lessons that could be used either on online learning or in person. The activity's strategy was a workshop that mainly focused on working and creating video lessons after giving a brief explanation on how to produce the video. The workshop also involves pre and post-test to assess the improvement of participants’ competence. This activity resulted in video lessons uploaded on the Youtube channel, and participants’ assessment scores improved from 65,8 to 76,9. Therefore, teachers involved in this social service admitted that they benefit from joining the workshop as they are now able to create exciting video lessons that might raise students’ enthusiasm and motivation in the learning process.